Embryonic development of Asiatic hard clam, Meretrix meretrix (Linnaeus, 1758) in hatchery condition - Laditah Duisan; Muhammad Baharudin; Vienna Anastasia Admodisastro; Tan, Aileen Shau Hwai; Julian Ransangan (Zoology Department, 2022)
Asiatic hard clam (Meretrix meretrix) is one of Malaysia's highly demanded bivalve species. Studies show that the clam population in some places, particularly in Marudu Bay is experiencing overexploitation. Thus, conservation effort through aquaculture is greatly required. The current study aimed to induce the spawning of Meretrix meretrix in hatchery condition using the thermal shock method. Ten specimens of the M. meretrix measuring between 5.00 and 7.00cm in shell length were induced to spawn by temperature shock at 5- 6 0C above the ambient temperature of seawater. Throughout the experiment, the clams were fed a live feed ration of mixed Isochrysis sp., Nannochloropsis sp., and Chaetoceros sp. at the ratio of 1:1:1 with the total concentration of 7.0 × 107 cells/broodstock twice a day at 07:00 and 17:00. The results demonstrated that the temperature shock induced 70% of the clams to spawn with a high fertilization rate (76.89%) but with a moderate hatching rate (47.39%). It was observed that the egg’s first cleavage (2-cell stage) was recorded 20 minutes after fertilization. The trochophore and D-shaped veligers formed 13 and 24 hours after fertilization. Veliger with cilia formed 2 days after fertilization. On the 6th day after fertilization, the veliger was observed to settle on the substrate. On the 10th after fertilization, spat began to develop umbo. Spats with complete umbo were observed 19 days after fertilization and on the 43rd day, the spats reached the juvenile stage. The present study demonstrates that the Meretrix meretrix clam can be induced to spawn by temperature shock. It took approximately 43 days for its larvae to fully develop into the juvenile stage. Further studies on improving the hatching rate, survival rate, and growth performance are necessary for economic seed production in the hatchery.